Historic and recent occurrences of pinnipeds in the Archipelago of the Azores - Silva, Mónica A. (2009)
The Archipelago of the Azores (Portugal) is located between 378 and 418N and 258 and 318W and crosses the Mid-Atlantic Ridge. It is the most isolated archipelago in the Atlantic, situated 1600 km west of mainland Portugal and 3500 km from the eastern coast of the United States of America. At present, the only population of seals occurring in the Portuguese territory is found on Desertas Islands, Archipelago of Madeira, where a colony of 24 Mediterranean monk seals, Monachus monachus (Hermann, 1779), still persists (Pires and Neves 2001). Nonetheless, historical accounts reported by Frutuoso (1983) dating from the early to late 1500s mention sightings of ‘‘sea wolves’’ (the old Portuguese folk term for the Mediterranean monk seal) at several sites along the Azorean Island of Santa Maria. Little is known about the occurrence of monk seals in this area over the past five centuries, but the species certainly did not escape deliberate killing by the first settlers. While the early monk seal reports by Frutuoso (1983) are the only reports referring to the presence of colonies of seals in the Azores, more recently several sightings and strandings of vagrant seals of other species have been noted.